Learning, structural instability and present value calculations - Mohammad Hashem Pesaran; Davide Pettenuzzo; Allan Timmermann (Deutsche Bundesbank, 2006)
Present value calculations require predictions of cash flows both at near and distant future points in time. Such predictions are generally surrounded by considerable uncertainty and may critically depend on assumptions about parameter values as well as the form and stability of the data generating process underlying the cash flows. This paper presents new theoretical results for the existence of the infinite sum of discounted expected future values under uncertainty about the parameters characterizing the growth rate of the cash flow process. Furthermore, we explore the consequences for present values of relaxing the stability assumption in a way that allows for past and future breaks to the underlying cash flow process. We find that such breaks can lead to considerable changes in present values.
Keywords: G22; G12; C11; 330; present value; stock prices; structural breaks; Bayesian learning; Dynamische Investitionsrechnung; Abzinsung; Stochastischer Prozess; Strukturbruch; Bayes-Statistik; Wertpapieranalyse; Schätzung; Theorie; USA